Using computers in archaeology : towards virtual pasts - Lock, G. R. (Gary R.) (Routledge, 2003)
Today, archaeologists are spending more and more time examining the past with the aid of computers. How does this increased dependence on technology affect the theory and practice of archaeology?Using Computers in Archaeology is a comprehensive review of computer applications in archaeology from the archaeologist's perspective. The book deals with all aspects of the discipline, from survey and excavation, to museums and education. Discussion covers the theoretical aspects of computer applications, with particular reference to GIS and the analysis of data, but technical jargon is kept to a minimum. With numerous illustrations, case-studies and examples, Using Computers in Archaeology is a timely introduction to this increasingly important area of archaeology, catering both for the student and the experienced archaeologist.